Conversational Implicature in “The Holdovers” Movie: Pragmatic Approach Directed by Alexander Payne - Ainiyah, Nur Rohmatul; Sholichah, Norma Ita (English Education and Literature Journal (E-Jou), 2025)
The goals of this research to examine conversational implicature in "The Holdovers" movie. This study examines conversational implicatures in The Holdovers 2023 movie directed by Alexander Payne. This study employed using a descriptive qualitative method, and researchers used Grice's theory to analyze many types of conversational implicature and the maxim of violation, which entails some steps the first, the researcher viewing the film, second, the researcher identifying implicature-containing sentences, and finally, the researcher then deciphered the meanings that were implied in the conversation. The findings indicate that there were 21 data points violation maxim from The Holdovers movie, the most frequent infraction is the relation maxim (7 data points), which is followed by the quantity maxim (6 data points), the quality maxim (6 data points), and the way maxim (2 data points). These violations often carried hidden meanings such as sarcasm, humorous, soft criticism, or emotional messages. These hidden meanings helped show how the characters express feelings or avoid conflict without speaking directly. This study advances the subject of pragmatics by demonstrating how indirect language in educational encounters may expose power dynamics, personal views, and generational communication gaps. Future research expected into implicature in other educataional media or actual classrooms. By comparing the two, we may gain a greater understanding of how individuals speak, express themselves, and deal with communication issues in education